Bagaimana Menerapkan Life Skills dan Ngerti, Ngrasa, Nglakoni Pada Worksheet Digital Berbasis Integrated-Science - Astuti Wijayanti; Tias Ernawati (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2021)
Science is a field of study that is closely related to daily life. However, students are less skilled and have difficulty connecting science concepts with problem-solving in their environment. This article is a Define phase that aims to describe how to apply life skills and understand, feel, and trace from the teachings of Ki Hajar Dewantara on integrated science-based digital worksheets in science learning. Data collection techniques using documentation that is from the study of literature about integrated science, lifeskill and the teachings of Ki Hajar Dewantara. Integrated science-based digital worksheets that are developed by applying life skills and ngerti, ngrasa, nglakoni can be displayed with a variety of innovative learning models. Application of the steps of the model will be able to bring up the type of life skills that are developed and also develop tringo in the learning activities of students. ÃÂ